2012
DOI: 10.1097/fjc.0b013e31823c0bed
|View full text |Cite
|
Sign up to set email alerts
|

No Significant Effect of Ginkgo Biloba Special Extract EGb 761 in the Treatment of Primary Raynaud Phenomenon

Abstract: EGb 761 treatment showed an excellent safety profile in patients with RD but could not demonstrate a statistically significant reduction in clinically relevant symptoms compared with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…In addition, a non-controlled observational study with severe RP and refractory ischaemic skin ulcers revealed healing rates of > 50 % within 2 -6 weeks of treatment with alprostadil [ESM 2, 2]. Other prostanoids (e.g., epoprostenol, treprostinil) have also been shown to improve symptoms and digital ischaemia in RP patients [ESM 2,3,7]. Consequently, the 2009 recommendations of the EU-LAR Scleroderma Trials and Research group (EUSTAR) for the treatment of systemic sclerosis advocate prostanoid infusions for patients with severe SSc-related RP, which is often characterised by extensive structural vascular damage and which manifests with painful digital ischaemia, skin ulcers or gangrene [ ESM 2,8].…”
Section: Vasodilator Therapymentioning
confidence: 99%
“…In addition, a non-controlled observational study with severe RP and refractory ischaemic skin ulcers revealed healing rates of > 50 % within 2 -6 weeks of treatment with alprostadil [ESM 2, 2]. Other prostanoids (e.g., epoprostenol, treprostinil) have also been shown to improve symptoms and digital ischaemia in RP patients [ESM 2,3,7]. Consequently, the 2009 recommendations of the EU-LAR Scleroderma Trials and Research group (EUSTAR) for the treatment of systemic sclerosis advocate prostanoid infusions for patients with severe SSc-related RP, which is often characterised by extensive structural vascular damage and which manifests with painful digital ischaemia, skin ulcers or gangrene [ ESM 2,8].…”
Section: Vasodilator Therapymentioning
confidence: 99%
“…Administration of wormwood (Artemisia absinthium L.) and Artemisia argyi H extract helped in restoring enzyme activities involved in the regulation of some neurotransmitters. The extract effectively improved the decline of the SOD level and increased the GSH level in oxidative stress [36,37]. The oxidative stress biomarkers, like SO, CAT and GSH levels in the test animals were elevated by pretreatment with extracts, whereas MDA levels were reduced.…”
Section: Discussionmentioning
confidence: 91%
“…Der Behandlungseffekt in der Plazebogruppe war aber völlig vergleichbar. So belegte die Studie nicht die Wirksamkeit von Ginkgo, sondern einen besonders ausgeprägten Plazeboeffekt für Maßnahmen bei diesem Krankheitsbild [18].…”
Section: Labordiagnostikunclassified